Radial variation of the stellar mass functions in the globular clusters M15 and M30: clues of a non-standard IMF?. Issue 2 (10th September 2020) - Cadelano, M; Dalessandro, E; Webb, J J; Vesperini, E; Lattanzio, D; Beccari, G; Gomez, M; Monaco, L
ABSTRACT: We exploit a combination of high-resolution Hubble Space Telescope and wide-field ESO-VLT observations to study the slope of the global mass function (α G ) and its radial variation (α( r )) in the two dense, massive and post core-collapse globular clusters M15 and M30. The available data set samples the clusters' main sequence down to ∼0.2 M⊙ and the photometric completeness allows the study of the mass function between 0.40 M⊙ and 0.75 M⊙ from the central regions out to their tidal radii. We find that both clusters show a very similar variation in α( r ) as a function of clustercentric distance. They both exhibit a very steep variation in α( r ) in the central regions, which then attains almost constant values in the outskirts. Such a behaviour can be interpreted as the result of long-term dynamical evolution of the systems driven by mass-segregation and mass-loss processes. We compare these results with a set of direct N -body simulations and find that they are only able to reproduce the observed values of α( r ) and α G at dynamical ages ( t / t rh ) significantly larger than those derived from the observed properties of both clusters. We investigate possible physical mechanisms responsible for such a discrepancy and argue that both clusters might be born with a non-standard (flatter/bottom-lighter) initial mass function.